The Effect of Exercise Consultation Program On Physical Activity Level in Elderly People at Darussalam Community Health Center, North Sumatra - Siregar, Rinco; Gultom, Rumondang; Saragih, Frida Liharis (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Background : It is importan to promote physical activity for elderly people, but to improve level of physicalactivity of elderly people is a challange for health workers. Purpose : The purpose of this quasi- experimentalstudy was to determine the effect of exercise consultation program by using Transtheoretical Model (TTM)approach on physical activity level in elderly people at Darussalam’ s Community Health Center. Researchmethod :The two comparison groups for this study were purposively designed for pre-test/post-test procedures;sixty elderly people at Darussalam’s Community Health Center with randomly allocated into the experimental(30 people) and the control (30 people) groups. While the experimental group received the exercise consultationfor 8 weeks, the control group received routine care. Physical Activity Scale for Elderly (PASE) was use toassess the the physical activity of elderly. Comparative assessments on differences in level of physical activityboth within group using Wilcoxson macthed-pairs and between group using Mann Withney U Test. Results :The results of this study found that after receiving exercise consultation program, level of physical activity inelderly people significantly increased in the experimental group (P < 0.05), but there was no significantdifference in the control group. Between groups, level of physical activity significantly increased afterreceiving the exercise consultation while no change was found among those who did not (P <0.05).Conclusion: The exercise consultation program by using TTM approach could increase level of physicalactivity of elderly people.